Protocolo para adequação da terapia nutricional enteral de idosos internados em unidade de terapia intensiva - Feitosa, Gina Araújo Martins (2022)
Introduction: Population aging has been the biggest demographic trend around the world. This phenomenon has been occurring at an accelerated pace, which contributes to the growth in the rates of hospitalized elderly people, demanding beds in the Intensive Care Unit. It is known that the ideal supply of enteral nutrition can improve clinical outcomes in critically ill patients, denoting the importance of developing enteral nutrition protocols. Objectives: To carry out an integrative review of the literature on the use of protocols in enteral nutritional therapy in critically ill elderly people; develop a nutritional protocol for hospitalized elderly in critical condition and using Enteral Nutritional Therapy; validate the content of the protocol by expert judges. Method: This is a methodological study of content construction and validation, whose first stage consisted of an integrative literature review to synthesize the main scientific evidence related to the theme; the second phase involved the elaboration of an enteral nutrition protocol; the third and final step was content validation by expert judges. This was possible through the Appraisal of Guidelines for Research and Evolution II (AGREE II) instrument. Results: An integrative review article “Use of enteral nutrition protocols in critically ill elderly patients: an integrative review” was produced; a protocol with approaches that involved diagnosis (nutritional screening, nutritional assessment and nutrition diagnoses), therapeutic plan (pillars for nutritional initiation and progression, and management of intercurrences) and follow-up (nutritional reassessment, nitrogen balance and updating of nutritional goals). Validation was carried out by 6 expert judges, obtaining percentages of 99.07% for Domain 1 (scope and purpose); 93.51% for Domain 2 (stakeholder engagement); 93.75% for Domain 3 (development rigor); 96.29% for Domain 4 (clarity of presentation); 95.13% for Domain 5 (applicability); and 100% for Domain 6 (editorial independence). In the global assessment, the judges judged the protocol with a maximum score (7) or submaximal (6), recommending the use of the guideline. In order to meet the judges' considerations and improve the quality of the guideline, adjustments and additions were made to the protocol regarding the items: use of systematic methods to search for evidence (item 7), evidence selection criteria (item 8), recommendations specific and unambiguous instructions (item 15), description of facilitating factors and barriers to the application of the protocol (item 18), as well as a general revision of the spelling and wording of the contents and an increase in the font of the flowcharts. Final considerations: The integrative review identified that nutritional therapy was optimized after the implementation of nutritional protocols in the ICU. The validation of the protocol's content by expert judges provided greater reliability in the dissemination of the product of this dissertation, highlighting the importance of its content to optimize nutritional practices for elderly people using enteral nutrition in the ICU, promoting improvement in their general condition. The importance of periodic updates of the document is emphasized and it is suggested that research be carried out with the implementation, monitoring and evaluation of the impact of the protocol, in order to provide the best practices in enteral nutritional therapy for critically ill elderly people.